Integration Formulas
Integration Formulas
Integration Formulas
org
Integration Formulas
1. Common Integrals Integrals of Exponential and Logarithmic Functions
Indefinite Integral ∫ ln x dx = x ln x − x + C
Method of substitution
x n +1 x n +1
∫ x ln x dx =
n
ln x − +C
∫ f ( g ( x)) g ′( x)dx = ∫ f (u )du n +1 ( n + 1)
2
Integration by parts
∫e
x
dx = e x + C
∫ f ( x) g ′( x)dx = f ( x) g ( x) − ∫ g ( x) f ′( x)dx
om
bx
∫ b dx =
x
Integrals of Rational and Irrational Functions +C
ln b
x n +1
∫ x dx = ∫ sinh x dx = cosh x + C
.c
n
+C
n +1
∫ cosh x dx = sinh x + C
t
1
∫ x dx = ln x + C
po
∫ c dx = cx + C
∫ xdx =
x2
2
+C
gs
lo
x3
∫ x dx =
2
+C
3
.b
1 1
∫ x2 dx = − x + C
eb
2x x
∫ xdx =
3
+C
ew
1
∫1+ x 2
dx = arctan x + C
1
∫
od
dx = arcsin x + C
1 − x2
Integrals of Trigonometric Functions
dc
∫ sin x dx = − cos x + C
∫ cos x dx = sin x + C
m
∫ tan x dx = ln sec x + C
∫ sec x dx = ln tan x + sec x + C
1
∫ sin ( x − sin x cos x ) + C
2
x dx =
2
1
∫ cos x dx = 2 ( x + sin x cos x ) + C
2
∫ tan
2
x dx = tan x − x + C
∫ sec
2
x dx = tan x + C
www.mathportal.org
( ax + b )n + 1
n
∫ ( ax + b ) dx = a ( n + 1) ( for n ≠ −1)
1 1
∫ ax + b dx = a ln ax + b
a ( n + 1) x − b
∫ x ( ax + b )
n
( ax + b )n+1
om
dx = 2
( for n ≠ −1, n ≠ −2 )
a ( n + 1)( n + 2 )
x x b
∫ ax + b dx = a − a 2 ln ax + b
.c
x b 1
∫ ( ax + b )2 dx = a 2 ( ax + b ) + a 2 ln ax + b
t
po
x a (1 − n ) x − b
∫ ( ax + b )n dx = a 2 ( n − 1)( n − 2)( ax + b )n−1 ( for n ≠ −1, n ≠ −2 )
x2
∫ ax + b dx =
1 ( ax + b )
2
− 2b ( ax + b ) + b 2
ln ax + b
gs
lo
a3 2
1 b2
.b
x2
∫ ( ax + b )2 dx = 3 ax + b − 2b ln ax + b −
a
ax + b
eb
x2 1 2b b2
∫ ( ax + b )3 dx = ln ax + b + −
a3 ax + b 2 ( ax + b )2
ew
1 ( ax + b )
3−n 2− n 1−n
x2 2b ( a + b ) b2 ( ax + b )
∫ ( ax + b ) n dx = − + − ( for n ≠ 1, 2,3)
a3 n−3 n−2 n −1
od
1 1 ax + b
∫ x ( ax + b ) dx = − b ln x
dc
1 1 a ax + b
∫ x 2 ( ax + b ) dx = − bx + b2 ln x
m
1 1 1 2 ax + b
∫ x 2 ( ax + b )2 dx = − a 2 + 2 − 3 ln
b ( a + xb ) ab x b x
Integrals involving ax2 + bx + c
1 1 x
∫ x 2 + a 2 dx = a arctg a
1 a−x
2a ln a + x for x < a
1
∫ x2 − a 2 dx = 1 x − a
ln for x > a
2a x + a
www.mathportal.org
2 2ax + b
arctan for 4ac − b 2 > 0
2
4ac − b 4ac − b 2
1 2 2ax + b − b 2 − 4 ac
∫ ax 2 + bx + c dx = 2 ln for 4ac − b 2 < 0
b − 4ac 2 ax + b + b 2 − 4ac
− 2 for 4ac − b 2 = 0
2ax + b
om
x 1 b dx
∫ ax 2 + bx + c dx = 2a ln ax ∫
2
+ bx + c − 2
2 a ax + bx + c
m 2 2an − bm 2ax + b
ln ax + bx + c + arctan for 4ac − b 2 > 0
.c
2 a a 4ac − b 2
4ac − b 2
mx + n
m 2an − bm 2ax + b
t
∫ ax 2 + bx + c dx = 2a ln ax + bx + c + a b2 − 4ac arctanh b2 − 4ac for 4ac − b < 0
2 2
po
m 2an − bm
ln ax 2 + bx + c − for 4ac − b 2 = 0
2a a ( 2 ax + b )
∫
1
dx =
2ax + b gs +
( 2 n − 3 ) 2a
2 ∫
1
( n − 1) ( 4ac − b ) ( ax 2 + bx + c )n−1
dx
lo
n n−1
( ax 2
+ bx + c ) ( n − 1) ( 4ac − b2 )( ax 2 + bx + c )
.b
1 1 x2 b 1
∫x dx = ln 2 − ∫ 2 dx
( ax 2
+ bx + c ) 2c ax + bx + c 2c ax + bx + c
eb
ew
cx x 2x 2
2
∫
2 cx
x e dx = e
c c 2 + c3
−
dc
1 n cx n n −1 cx
∫x x e − ∫ x e dx
n cx
e dx =
c c
m
i
ecx ∞ cx
( )
∫ x dx = ln x + ∑ i ⋅ i!
i =1
1 cx
∫e
cx
ln xdx = e ln x + Ei ( cx )
c
ecx
∫ e sin bxdx =
cx
( c sin bx − b cos bx )
c 2 + b2
ecx
∫ e cos bxdx =
cx
( c cos bx + b sin bx )
c 2 + b2
ecx sin n −1 x n ( n − 1)
∫ e sin xdx = ∫e sin n −2 dx
cx n cx
2 2
( c sin x − n cos bx ) + 2 2
c +n c +n
www.mathportal.org
om
∫ ln x = ln ln x + ln x + ∑
n =2 i ⋅ i !
dx x 1 dx
∫ ( ln x )n =− n −1
+
n − 1 ∫ ( ln x )n −1
( for n ≠ 1)
.c
( n − 1)( ln x )
t
m +1 ln x 1
∫
m
x ln xdx = x − ( for m ≠ 1)
po
m + 1 ( m + 1) 2
n
x m+1 ( ln x ) n
gs
n n −1
∫ x ( ln x ) ∫
m
dx = − x m ( ln x ) dx ( for m ≠ 1)
m +1 m +1
lo
( ln x )n ( ln x )n+1
∫ dx =
n +1
( for n ≠ 1)
.b
x
2
ln x n ln x n ( )
eb
∫ x dx = 2n ( for n ≠ 0 )
ln x ln x 1
∫ xm dx = − ( m − 1) xm−1 − ( m − 1)2 xm−1 ( for m ≠ 1)
ew
( ln x )n ( ln x )n n ( ln x )n−1
∫ dx = −
( m − 1) x m−1 m − 1 ∫ x m
+ dx ( for m ≠ 1)
od
xm
dx
∫ x ln x = ln ln x
dc
dx ∞
( n − 1)i ( ln x )i
∫ xn ln x = ln ln x + ∑
i
( −1)
m
i =1 i ⋅ i!
dx 1
∫ x ( ln x )n =−
( n − 1)( ln x )n−1
( for n ≠ 1)
x
∫ ln ( x ) ( )
+ a 2 dx = x ln x 2 + a 2 − 2 x + 2a tan −1
2
a
x
∫ sin ( ln x ) dx = 2 ( sin ( ln x ) − cos ( ln x ) )
x
∫ cos ( ln x ) dx = 2 ( sin ( ln x ) + cos ( ln x ) )
www.mathportal.org
om
∫ sin xdx = 3 cos x − cos x
3 3
dx 1 x π
1 3
∫ sin 2 x cos x = − sin x + ln tan 2 + 4
∫ cos xdx = sin x − 3 sin x
3
dx 1 x
.c
dx x ∫ sin x cos2 x = cos x + ln tan 2
∫ sin x xdx = ln tan 2
t
dx
∫ sin 2 x cos2 x = tan x − cot x
po
dx x π
∫ cos x xdx = ln tan 2 + 4 sin( m + n) x sin( m − n) x
∫sin mxsin nxdx = − 2( m+ n) + m2 ≠ n2
dx
∫ sin 2 x xdx = − cot x gs 2( m − n)
cos ( m + n) x cos ( m − n) x
∫sin mxcos nxdx = − 2( m + n) − m2 ≠ n2
lo
dx
∫ cos2 x xdx = tan x 2( m − n)
sin ( m + n) x sin ( m − n) x
.b
dx cos x 1 x
∫ sin 3 x = − 2sin 2 x + 2 ln tan 2 ∫ cos mxcos nxdx = 2( m + n) +
2( m − n)
m2 ≠ n2
eb
dx sin x 1 x π cos n +1 x
∫ cos3 x = 2 cos2 x + 2 ln tan 2 + 4 ∫ sin x cos xdx = −
n
n +1
ew
1 sin n +1 x
∫ sin x cos xdx =
n
∫ sin x cos xdx = − 4 cos 2 x n +1
1 3
∫ sin x cos xdx = 3 sin x ∫ arcsin xdx = x arcsin x + 1 − x2
od
1
∫ arctan xdx = x arctan x − 2 ln ( x )
2
+1
x 1
∫ sin x cos xdx = 8 − 32 sin 4 x
2 2
1
m